(untitled) (River Edge, NJ, 2001)
This volume describes advances in both experimental and theoretical treatments in the field of energy transfer processes that are relevant to various fields, such as spectroscopy, laser technology, phosphors, artificial solar energy conversion, and photobiology. It presents the principles and available techniques through specific examples. In addition, it examines current and possible applications, including the most recent developments, and projects future advances and research possibilities in the field.
Keywords: Energy transfer,Charge transfer,Electronic excitation; Chuyển điện tích,Điện tử kích thích